Dampak Implementasi Kebijakan Renewable Energy Directive II terhadap Hubungan Indonesia - Uni Eropa - Bukkang, Yun Silva; Bt. Mamma, Beche; Burhan, Zulkhair (Journal of International and Local Studies, 2023)
This research will write down the impact of implementing the Renewable Energy Directive II policy issued by the European Union to regulate the use of renewable energy as a form of the European Union's commitment to Sustainable Development Goals (SDGs). In the Renewable Energy Directive II Policy issued by the European Union, it is stated that palm oil causes deforestation or environmental damage. Indonesia, which has long established economic cooperation with the European Union, especially in the export-import of palm oil, as the world's largest producer of palm oil, feels discriminated against the policy issued. Indonesia gets the country's largest foreign exchange from exports of palm oil and its derivatives which will then have a major impact on the decline in imports of palm oil by the European Union after the issuance of this policy. This research question is "What is the impact of the implementation of the Renewable Energy Directive II policy on relations between Indonesia and the European Union?" to answer the questions in this study, researchers used the concept of International Political Economy by Robert Gilpin in explaining the results of this study. This study uses qualitative research methods using secondary data sources. The results of this study will answer the forms of tense relations between Indonesia and the European Union and what factors influence these tensions to occur. This research will also explain the beginning of the cooperation between Indonesia and the European Union and how the relationship was before and after the Renewable Energy Directive II policy was made.